Trust, Innovation and Risk: a contextual inquiry into teaching practices and the implications for the use of technology - Donna Lanclos (Irish Journal of Technology Enhanced Learning, 2019)
If we are to bring about lasting changes around the use of technology in teaching and learning in colleges and universities, we need to understand the practices that staff undertake and the challenges they face. Effective and sustained change comes from a place of working in service to pedagogies, and practices that support and surround learning and teaching. In order to better understand these issues Jisc commissioned research to gain more understanding about practice around learning and teaching and gaining insights beyond the technology-led.